EFEKTIVITAS PROGRAM G-ONLINE DALAM MEWUJUDKAN SMART CITY DI KABUPATEN SUMENEP - Aliffikri Nasrullah; Irma Irawati Puspaningrum; Alqaf Harto Maryono (PUBLIC CORNER, 2021)
AbstractThe Government Online (G-Online) program that has been implemented to start its e-governmentsystem in the form of public service using the use of Information Technology (IT) systems hasmade it easier for OPDs in the scope of government, where at this time Sumenep Regency is partof the Movement Towards 100 Smart City Indonesia organized by the Ministry of Communicationand Information of the Republic of Indonesia. The initiation of smart city implementation inSumenep Regency is also based on the needs of the local government in realizing integrated andefficient public services that have been preceded by the implementation of e-government. Thisresearch method uses descriptive qualitative research focusing on four aspects of effectiveness,namely 1) Aspects of tasks or functions, 2) Aspects of plans or programs, 3) Aspects of provisionsand regulations, 4) Aspects of goals or ideal conditions. The results show that the effectiveness ofthe G-Online program has a big influence on the Smart City concept developed in SumenepRegency because in the Smart City itself the use of Information Technology (IT) systems isfundamental in its implementation, therefore the G-Online program continues to be developed sothat can grow good and efficient results in realizing Smart City in Sumenep Regency.Keywords: Effectiveness, G-Online Program, Smart CityAbstrakProgram Government Online (G-Online) yang telah diterapkan untuk mengawali sistem egovernmentnya berupa pelayan publik dengan menggunakan pemanfaatan sistem InformasiTeknologi (IT) telah memberi kemudahan bagi para OPD di lingkup pemerintahan, dimana padasaat ini Kabupaten Sumenep menjadi bagian dari Gerakan Menuju 100 Smart City Indonesia yangdi selenggarakan oleh Kementerian Komunikasi dan Informatika Republik Indonesia. Inisiasipelaksanaan smart city pada Kabupaten Sumenep juga dilandasi oleh kebutuhan pemerintahdaerah dalam mewujudkan pelayanan publik yang terintegrasi dan efisien yang telah didahuluidengan penyelenggaraan e-government. Metode penelitian ini menggunakan deskriptif kualitatifdengan fokus penelitian empat aspek efektivitas, yaitu 1) Aspek tugas atau fungsi, 2) Aspekrencana atau program, 3) Aspek ketentuan dan peraturan, 4) Aspek tujuan atau kondisi ideal. Hasilpenelitian menunjukkan bahwa efektivitas program G-Online berpengaruh besar dalam konsepSmart City yang di kembangkan di Kabupaten Sumenep sebab dalam Smart City sendiripenggunaan sistem Informasi Teknologi (IT) adalah hal yang mendasar dalam penerapaanya, olehsebab itu program G-Online terus dikembangkan agar dapat menumbuhkan hasil baik dan efisiendalam mewujudkan Smart City di Kabupaten Sumenep.Kata Kunci : Efektivitas, Program G-Online, Smart City